Perencanaan Strategis dalam Meningkatkan Kinerja Organisasi : Sebuah Kajian Literatur - Hairunisa Hairunisa; Alek Alaikal Hasan; Bima Kurniawan; Ana Qonita; Muhammad Nuryan Firnanda; Muhammad Firdan Abrori; Mu’alimin Mu’alimin (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The role of strategic planning plays a crucial role in improving organizational performance as well as in its implementation. This researcher aims to examine the role and implementation of strategic planning in improving organizational performance in the context of education through a literature review approach to five selected articles published between 2022 and 2024. The results of this study indicate that the role and implementation of strategic planning act as the main foundation in determining the direction of the organization, ensuring alignment between vision, mission, and operational actions. Effective implementation of this strategic plan requires resource coordination, clear communication, and leadership that is able to motivate and direct time.